2015
DOI: 10.1002/pen.24196
|View full text |Cite
|
Sign up to set email alerts
|

Damping elastomer with broad temperature range based on irregular networks formed by end‐linking of hydroxyl‐terminated poly(dimethylsiloxane)

Abstract: Irregular networks based on the condensation reaction of hydroxyl‐terminated poly(dimethylsiloxane) with cross‐linkers were investigated. The networks have excellent damping properties in a wide temperature range utilizing the viscoelastic relaxation of the irregular network with dangling chains. NMR Cross‐link Density Spectroscopy was used to explore the weight fraction of pendant chains and elastic chains in the elastomer. The transverse relaxation time for the elastomer was studied to explore the influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…E′ and E″ represent the storage modulus and loss modulus, respectively [7]. High-performance viscoelastic damping materials should meet the requirement of tan δ > 0.3 over a broad damping temperature range of at least 60–80 °C [8]. …”
Section: Introductionmentioning
confidence: 99%
“…E′ and E″ represent the storage modulus and loss modulus, respectively [7]. High-performance viscoelastic damping materials should meet the requirement of tan δ > 0.3 over a broad damping temperature range of at least 60–80 °C [8]. …”
Section: Introductionmentioning
confidence: 99%
“…Some studies on molecular dynamics have found that tanδ consists of three molecular motions (LSM, Sub-rouse, Rouse model) and the area of tanδ is influenced by them together [24][25][26]. Generally, the area where tanδ >0.3 is called the effective damping region [27,28]. In this paper, tanδ max and tanδ peak area (TA) were used to evaluate the damping properties and other damping parameters of blends are listed in Table 2.…”
Section: Molecular Dynamics Of Pbma/pr Compositesmentioning
confidence: 99%
“…Rubber damping materials used for reducing unwanted noises and preventing vibration failure are becoming increasingly significant in all kinds of motor vehicles, equipments and instruments, automatic office equipments, and household appliances. [1][2][3][4] High performance damping materials should meet the requirement of tanδ > 0.3 over a wide temperature range of 40-60 C. [5,6] However, a single rubber cannot satisfy the performance requirements of high damping materials attributed to the narrow effective damping temperature range. [7] During recent years, a large substantial amount of studies have been devoted to the improvement of damping property for rubber damping materials by polymer blending [8][9][10] or filler addition.…”
Section: Introductionmentioning
confidence: 99%